Pengaruh Penyetelan Sudut Toe dan Tekanan Ban Terhadap Hasil Uji Side Slip Tester pada Mikrobus Isuzu NLR 55B LX - Ni Putu Yana Teja Pertiwi; Joko Winarno; Mochamad Syamsiro; Sri Gati Hutomo (Universitas Sarjanawiyata Tamansiswa, 2026)
Front wheel alignment and tire pressure are important factors affecting vehicle stability, comfort, and driving safety during operation. This study aimed to analyze the effect of toe angle adjustment and tire pressure variation on side slip test results in the Isuzu NLR 55B LX microbus. The research employed an experimental method conducted at the Motor Vehicle Testing Unit of the Department of Transportation of Magelang City using an HPA side slip tester manufactured in 2004. The experimental variables consisted of three toe angle variations (-0°25′, +0°15′, and +0°25′) and three tire pressure variations (35, 50, and 65 psi), while the front wheel deviation data were analyzed descriptively and comparatively. The results showed that non-standard toe angle and tire pressure settings produced side slip values exceeding the allowable roadworthiness threshold of ±5 mm/m, with the highest deviation reaching -14.7 mm/m under low tire pressure and below-standard toe angle conditions. In contrast, the standard toe angle setting (+0°15′) with a tire pressure of 50 psi produced a side slip value of 3.6 mm/m, which remained within the acceptable threshold. Both under-inflated and over-inflated tire conditions were found to increase wheel deviation due to changes in tire-road contact characteristics. This study confirms that proper toe angle adjustment and tire pressure settings play an important role in maintaining vehicle stability, improving driving safety, and extending tire service life.